2022
DOI: 10.1111/jomf.12831
|View full text |Cite
|
Sign up to set email alerts
|

Frontline love: Romantic partners of frontline doctors and nurses during the New York City COVID‐19 outbreak

Abstract: Objective: This qualitative study's aim was to learn how the spouses and romantic partners of frontline doctors and nurses dealt with the acute stress of the outbreak; the kinds of support they provided when the frontliners had to navigate COVID-19 at their hospitals; and, according to their perceptions, how this crisis impacted their relationship. Background: This study focused on the partners of frontliners working in hospitals during the crisis of the coronavirus outbreak in New York City (NYC)-one of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Others reported the financial burden of flying back and forth to the UK every school holiday in order to care for boarding school children. Our finding that partners took on more childcare responsibilities due to their diplomatic spouses having increased workloads echoed findings from partners of other frontline workers during the pandemic: for example, partners of healthcare workers have reported that their partners' increased workload meant that they had to take on more of the domestic responsibilities that were previously shared [45,46].…”
Section: Plos Onesupporting
confidence: 72%
“…Others reported the financial burden of flying back and forth to the UK every school holiday in order to care for boarding school children. Our finding that partners took on more childcare responsibilities due to their diplomatic spouses having increased workloads echoed findings from partners of other frontline workers during the pandemic: for example, partners of healthcare workers have reported that their partners' increased workload meant that they had to take on more of the domestic responsibilities that were previously shared [45,46].…”
Section: Plos Onesupporting
confidence: 72%
“…In addition to gender differences, we expect changes in subjective sexual well-being to vary in relation to several other social location factors. Economic problems can affect marital quality and stability (Siegel and Dekel 2022), and job precarity has been pervasive because of rapidly shifting economic conditions during the COVID-19 pandemic (Rao 2020). Labor force participation in the United States fell more severely for women than for men (Collins et al 2021), and gender equity spanning work, home life, and parenting has deteriorated (Lyttelton et al 2022; Ruppanner et al 2021; Yavorsky et al 2021).…”
Section: Social Standing Meets Stressmentioning
confidence: 99%
“…A warm partner may serve as a system of support by communicating feelings, remaining positive, and facing issues together which may help alleviate burdens stemming from a stressful situation (Chakraborty et al, 2021). Having a loving, supportive partner may help to keep a positive perspective during times of crisis that could even lead to a stronger bond within the marriage (Chakraborty et al, 2021;Siegel & Dekel, 2022).…”
Section: Chapter 4 Discussionmentioning
confidence: 99%